Prototype Media Interaktif untuk Menanamkan Nilai Pancasila untuk Anak Usia Dini - Mahyumi Rantina; Febriyanti Utami; Windi Dwi Andika (Program Studi Pendidikan Islam Anak Usia Dini, UIN Sunan Ampel Surabaya, 2022)
The purpose of this study was to produce a valid interactive media prototype for instilling Pancasila values ​​in early childhood. This type of research is R&D with the Borg and Gall model with procedures for needs analysis, prototype design, development, and evaluation of implementation. Evaluation technique used with Tessmer evaluation. The data collection technique used a walkthrough which was assessed by the media validator and material validator. Based on the results of research from experts, namely material experts and media design experts with very valid categories with a feasibility percentage of 92.3% and 99.99% respectively, so that the product is valid in terms of visual media, audio media, aspects of typography, aspects of language, aspects of programming, aspects of presentation and feasibility of the content of Pancasila values. From the results of this study, interactive media for instilling Pancasila values ​​in early childhood is valid to be used and utilized by teachers and parents